STRATEGI PROMOSI MIDNITE SALE DALAM UPAYA MENINGKATKAN NIAT KONSUMEN PADA PUSAT PERBELANJAAN - CHANDRA, ANITA MEGAWATI (JURNAL ILMIAH MAHASISWA MANAJEMEN, 2012)
This paper aims to clarify the role of midnite sale to efforts to improve consumer purchase intention. Analyzed using qualitative descriptive technique by citing data from various sources. The analysis shows that the life of a big city at night which is not much different life in the daytime much in use by retailers to make sales is by encouraging consumers make a purchase on the night. One way to do is hold the event on sale or sale at discounted prices in the evening. Therefore, by promoting shopping in the evening especially when the weekend much in demand by consumers. Moreover, when consumers feel they have many benefits especially financial benefits with a variety of spending cuts, causing consumers more interested in shopping. Through midnite sale promotion strategy will encourage consumers to shopping as it provides many pieces. To that end, the presence of midnite sale to increase intentions consumer buying.